Low sensitivity of reproductive life-stages in the Pacific oyster (Crassostrea gigas) to abamectin. (September 2017) - Falkenberg, Laura J.; Wrange, Anna-Lisa; Kinnby, Alexandra; Havenhand, Jon N.; Lockyer, Antony; Styan, Craig A.
Abstract: Hard surfaces submerged in the marine environment often become colonised by macro-organisms unless the surfaces have some form of biofouling protection. While protective paints that contain tributyltin or copper work well to prevent biofouling, release of these materials into the environment has been shown to have wider negative impacts. Consequently, new low-release antifouling paints are being developed with alternative active ingredients, such as avermectins, yet little is known about their potential effects on non-target organisms in marine environments. Here we investigated the toxicity of a key avermectin, specifically abamectin, on several aspects of reproduction (sperm motility, fertilisation success, early larval development) in the Pacific oyster, Crassostrea gigas . Oyster reproduction was generally insensitive to the low concentrations of abamectin, although greater concentrations of abamectin did negatively affect all three endpoints – LOECs were 1000 μg l −1, 500 μg l −1, and 100 μg l −1 abamectin for sperm motility, fertilisation success, and larval development, respectively. A similar pattern was found in the EC50 s of the three endpoints (mean ± SE) 934 ± 59 μg l −1, 1076.26 ± 725.61 μg l −1, and 140 ± 78 μg l −1 abamectin (sperm motility, fertilisation success, and larval development, respectively). Together, these results clearly indicate that of the three endpoints considered, larval development was more sensitive to abamectin (lower LOEC, EC50 ) than fertilisation success and sperm motility. Although more data are needed from a wider range of marine species and environments to fully assess potential toxicity effects on non-target organisms, our results highlight the potential utility of abamectin in low-release antifouling paints. Graphical abstract: Highlights: Antifouling paints protect structures submerged in marine environments. Currently-used additives toxic to non-target organisms, meaning alternatives needed. An emerging alternative is abamectin, yet little is known regarding its toxicity. Oyster sperm reproductive parameters generally robust to moderate enrichment. Low-release antifouling paints with abamectin may not affect non-target organisms.